Radiological safety of workers for the beta-nuclide removal treatment of the mixed waste from Wolsong nuclear power plant - Ja Yeong Yoon; Sia Hwang; Hee Reyoung Kim (Nuclear Engineering and Technology, 2025)
This study evaluates the radiological safety of the beta-nuclide removal process for mixed radioactive waste (waste resin, activated carbon, and zeolite) generated during the operation of Wolsong Unit 1. In addition, the potential for reducing worker radiation exposure in accident scenarios was investigated to optimize waste processing capacity. Using the VISIPLAN dose assessment code, external exposure was analyzed in scenarios involving the leakage of airborne radioactive particulates during the beta nuclide removal process. Internal exposure was assessed by taking into account the concentration of airborne radioactive particulates and effectiveness of the protective equipment. The 1 kW beta-nuclide removal reactor processes activated carbon and zeolite, while the 9 kW beta-nuclide removal reactor processes waste resin. Under the conditions of airborne radioactive particulates leakage, the maximum total dose rates for the 1 and 9 kW beta nuclide removal reactors reached 1.51 × 10−2 and 7.22 × 10−2 mSv/h, respectively. Based on the annual dose limit of 20 mSv over a five-year period, the permissible operating hours for the 1 kW and 9 kW reactors were determined to be 1325 h and 277 h, respectively. It is expected that these results will contribute to advances in radiation safety assessment techniques for reactor decommissioning and radioactive waste management.